The Dutch Architecture in Siberia. Is It Possible to Revitalize the Heritage of the Architect Van Loghem in Kemerovo? - Zakharova, Irina (project baikal, 2017)
The history of the industrial and urban development of Kemerovo is connected with a unique experiment in the establishment of the autonomous industrial colony of foreign workers “Kuzbass” in the early 1920s. The buildings designed by the Dutch functionalist architect Johannes van Loghem, who worked in the autonomous industrial colony, are of special value. The article tells about the unique Russian-Dutch heritage sites on the territory of the Kemerovo mine, which are currently in danger.
Keywords: the autonomous industrial colony “Kuzbass”; Johannes van Loghem; “Modern Movement”; Russian-Dutch architectural heritage; restoration